Analisis Pengeluaran Perkapita Dalam Upaya Peningkatan Pembangunan Manusia Di Sulawesi Tenggara Pada Tahun 2021 - Silvya Putri Wardyana; Prayudi Setiawan Prabowo (Universitas Negeri Surabaya, 2022)
This research was conducted to determine the effect of per capita expenditure in seeking to increase human development that occurred in Southeast Sulawesi in 2021. A simple linear regression analysis was used with cross-section secondary data. The results obtained from this study indicate that there is an influence between the idependent variabels and the dependent variabel used. The effect generated by per capita expenditure is positive and significant on the Human Development Index in Southeast Sulawesi Province. Keywords: Per capita expenditure, Human Development Index, A simple regression analysis